A Search for Sterile-Neutrino-Based Muon Neutrino Disappearance using the MicroBooNE Deep Learning Analysis - Mills, Joshua. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Physics.; Advisor: Taritree Wongjirad.; Committee: Georgia Karagiorgi, Hugh Gallagher, Hugo Beauchemin, and Roger Tobin.; Keywords: Physics, and Particle physics.